Issues in urban nursery facilities from childcare workers' awareness during the COVID-19 pandemic: Analysis of interview findings focused on ventilation behavior - Tanaka, Ineko; Matsuhashi, Keiko; Taneichi, Shinya (Japanese Journal of Health and Research, 2025)
【Background】It is difficult to secure sufficient indoor space and ventilation in nursery facilities located in city centers, raising concerns about infection risks for children and their caregivers. The purpose of this research is to sort out the challenges faced by nursery facilities by focusing on the infection prevention awareness of childcare workers before and after the COVID-19 pandemic and the environmental characteristics of the areas where the facilities were located.【Methods】We chose as research subjects five facilities in Yokohama City that showed differences in CO2 concentrations, temperature, and humidity based on our measurement results and which seemed to have varying levels of awareness of ventilation and infection prevention. We then conducted an interview survey of the directors of the facilities about measures employed to prevent infection with COVID-19, changes in their awareness before and after the pandemic, and other matters, such as difficulties they experienced trying to prevent infections.【Results】All nursery facilities were in areas where there was no need to worry about traffic noise or annoying people in the neighborhood with noise from the facility. However, windows were often opened to introduce fresh air in only three facilities. Additionally, there were facilities that could not freely open their windows for ventilation. Nevertheless, in both cases, awareness of the importance of ventilation improved after experiencing the COVID-19 pandemic.【Conclusion】The survey subjects responsible for facility management were earnestly seeking information and guidance on indoor air quality control, a finding that highlighted the need for providing information tailored to childcare workers.